Selective Wireless Power Transfer via Magnetic Resonant Coupling by Using Variable Impedance Circuit - Nakagawa, Takahiro; Sugimoto, Tomoya; Nozaki, Takahiro; Murakami, Toshiyuki (IECON 2018 44th Annual Conference of the IEEE Industrial Electronics Society, 2018)
Recently, Wireless Power Transfer (WPT) via Magnetic Resonant Coupling is especially focused around the world. Since a space will have a lot of devices in the future, WPT considering multiple devices will be required. It is important to consider not only power transfer efficiency but also power distribution when power is wirelessly transferred to multiple devices. The amount of received power in a receiver depends on the impedance of the receiver and the ratio of power distribution has the relation to the impedance. Conventional WPT system requires a few controllable repeaters and the large size of the receiver. In this paper, a variable impedance circuit for power distribution is proposed. Using the proposed circuit controllable by DC voltage, the problem for the conventional system is solved. In the future when WPT is popular, the circuit realizes electrically controllable power distribution.